Impact of Fixed Oil on Ostwald Ripening of Anti-Oral Cancer Nanoemulsions Loaded with Amomum kravanh Essential Oil - Yotsanan Weerapol; Suwisit Manmuan; Nattaya Chaothanaphat; Siriporn Okonogi; Chutima Limmatvapirat; Sontaya Limmatvapirat; Sukannika Tubtimsri (MDPI AG, 2022)
Recently, essential oil from Amomum kravanh (AMO) was reported to exert anti-oral cancer effects. Although it was more effective after being loaded into nanoemulsions, AMO without an Ostwald ripening inhibitor was unable to form stable nanoemulsions because of the Ostwald ripening phenomenon. In this study, we examined the influence of Ostwald ripening inhibitors, such as fixed oils and polyethylene glycol 4000 (PEG 4000), on nanoemulsion properties prepared by a phase inversion temperature method. Several fixed oils, including virgin coconut oil (VCO), palm oil (PMO), olive oil (OLO), and PEG 4000, were evaluated, and their Ostwald ripening inhibitory effects were compared. The results suggest that the type and ratio of AMO:fixed oils influence the formation and characteristics of nanoemulsions. PEG 4000 was unable to produce nanoemulsions; however, stable nanoemulsions with small droplet sizes were observed in preparations containing OLO and VCO at an AMO:fixed oil ratio of 80:20, which may be the result of specific molecular interactions among the components. Using an MTT assay, we demonstrated that the AMO:OLO (80:20) nanoemulsion produced the most significant cytotoxic effect on oral cancer cells with a percentage of 99.68 ± 0.56%. Furthermore, the AMO:OLO 80:20 nanoemulsion inhibits metastasis and induces oral cancer cell death through the intrinsic apoptosis pathway. In conclusion, AMO nanoemulsion with anti-oral cancer activity was successfully produced by varying the amount and type of fixed oils. In the future, this discovery may lead to the development of stable nanoemulsions employing additional volatile oils.